2019
DOI: 10.1039/c9ta00038k
|View full text |Cite
|
Sign up to set email alerts
|

Scalable one-step synthesis of N,S co-doped graphene-enhanced hierarchical porous carbon foam for high-performance solid-state supercapacitors

Abstract: N,S co-doped graphene-enhanced HPC is prepared by a facile one-step method, and exhibits superior electrochemical performances as a solid-state supercapacitor electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 60 publications
2
53
0
Order By: Relevance
“…A broader account of the synthesis of doped nanocarbons can be found elsewhere. [45,73,[98][99][100][101] In general, the heteroatom functionalization and doping are carried out using the following two strategies (Figure 4). a) Heteroatom-introducing strategy where heteroatoms are introduced into carbon matrix by post-treatment of the already formed carbon structures, including chemical activation, heat treatment under relevant atmosphere, microwave irradiation, plasma functionalization, etc.…”
Section: The Limited Density Of States At the Fermi Level (Dos(e F ))mentioning
confidence: 99%
“…A broader account of the synthesis of doped nanocarbons can be found elsewhere. [45,73,[98][99][100][101] In general, the heteroatom functionalization and doping are carried out using the following two strategies (Figure 4). a) Heteroatom-introducing strategy where heteroatoms are introduced into carbon matrix by post-treatment of the already formed carbon structures, including chemical activation, heat treatment under relevant atmosphere, microwave irradiation, plasma functionalization, etc.…”
Section: The Limited Density Of States At the Fermi Level (Dos(e F ))mentioning
confidence: 99%
“…While EDX elemental analysis results show that the pore‐engineering does not change the abundances of N and S significantly, we further probed their detailed configurations by high‐resolution N1s and S2p X‐ray photoelectron spectroscopy (XPS). Figure a shows that the N1s spectra of the carbon materials can be deconvoluted into four different peaks at 398.4, 400.5, 401.5, and 403.7 eV, which can be assigned to pyridinic‐, pyrrolic‐, graphitic‐, and oxidized‐N species, respectively (as illustrated in Figure c) . Further, the S2p spectra in Figure b can be split into two peaks.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 4a shows that the N1s spectra of the carbon materials can be deconvoluted into four different peaks at 398.4, 400.5, 401.5, and 403.7 eV, which can be assigned to pyridinic-, pyrrolic-, graphitic-, and oxidized-N species, respectively (as illustrated in Figure 4c). [18] Further, the S2p spectra in Figure 4b can be split into two peaks. The peaks at 163.9 and 165.2 eV can be assigned to S2p 3/2 and S2p 1/2 of SÀ C bonds (as illustrated in Figure 4c).…”
Section: Resultsmentioning
confidence: 97%
“…45 It has been reported that N-(pyridinic-and pyrrolic-N) and S-containing (sulfone and sulfoxide) species are assumed to be the main con¯gurations contributing the enhanced pseudocapacitance by Faradaic reactions, whereas quaternary-N can improve the electrical conductivity of carbon materials. 36,46 Additionally, the introduction of nitrogen atoms into carbon lattice can change the electron distribution of carbon material, resulting to a signi¯cant increase of active surface area accessible to the electrolyte. 46,47 The XPS analysis further con¯rms the successful doping of N and S, which could enhance the wettability and electrochemical activity of the N-S-HPC as well as providing extra pseudocapacitance contribution.…”
Section: -3mentioning
confidence: 99%
“…36,46 Additionally, the introduction of nitrogen atoms into carbon lattice can change the electron distribution of carbon material, resulting to a signi¯cant increase of active surface area accessible to the electrolyte. 46,47 The XPS analysis further con¯rms the successful doping of N and S, which could enhance the wettability and electrochemical activity of the N-S-HPC as well as providing extra pseudocapacitance contribution. 48 The high doping content of both N and S elements also suggests that the use of thiourea as the dopant is e±cient and cost-saving.…”
Section: -3mentioning
confidence: 99%